What do we know about preventing school violence? A systematic review of systematic reviews - Lawrence, Cayleigh (2017)
Many children across the world are exposed to school violence, which undermines their right to education and adversely affects their development. Studies of interventions for school violence suggest that it can be prevented. However, this evidence base is challenging to navigate. We completed a systematic review of interventions to reduce four types of school violence: (a) peer violence; (b) corporal punishment; (c) student-on-teacher violence and (d) teacher-on-student violence. Reviewers independently searched databases and journals. Included studies were published between 2005 and 2015; in English; considered school-based interventions for children and measured violence as an outcome. Many systematic reviews were found, thus we completed a systematic review of systematic reviews. Only systematic reviews on interventions for intimate partner violence (IPV) and peer aggression were found. These reviews were generally of moderate quality. Research on both types of violence was largely completed in North America. Only a handful of programmes demonstrate promise in preventing IPV. Cognitive behavioral, social-emotional and peer mentoring/mediation programmes showed promise in reducing the levels of perpetration of peer aggression. Further research needs to determine the long-term effects of interventions, potential moderators and mediators of program effects, program effects across different contexts and key intervention components